Pengembangan Sistem Aplikasi Dalam Jaringan Untuk Tes Diagnostik Fluida Statis Pada Sekolah Menengah Atas - Hartono, Puji; Sugiyanto, Sugiyanto; Nugroho, Sunyoto Eko (UPEJ Unnes Physics Education Journal, 2021)
In this research, an online application system was developed for static fluid diagnostic tests in high schools. The aim of this study is to develop an online diagnostic test and determine its feasibility. This research is classified as research and development research. The development model used in this study is the Borg and Gall model. The resulting product supports several features, including registration, user management, question bank management, test bank management, test result management, mathematical symbols, and development support. From data collection using the scale method. There are several aspects tested in determining the feasibility of software, including functional suitability, performance efficiency, compatibility, usability, reliability, security, maintainability, portability, effectiveness, efficiency, satisfaction. The results show that an average percentage of feasibility is 90.07%. Based on these results, the developed diagnostic test can be used to identify student learning difficulties.